Peranan Olahraga Tradisional Terhadap Pelestarian Adat Dan Budaya - Kostermans, Ding (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2016)
The objective of this research is willing to know to empower the traditional games. The location is in Tenggarong in 2016. The results of it are: (1). The nine traditional competition especially in Kutai, (2). The competition is to defend the ones which have been isolated, (3). The eventalso introduced the traditional sport, (4).The location of the competition in three locations, bank of Sungai Mahakam in Tenggarong, in Telcom office and Tenggarong youth field followed by all subsdistricts in Kukar, (4). The name is Erau Internasional Folk Art Festival (EIFAF). The suggestions of this research are: (1). To support the competition the traditional games, (2). To maintain the traditional games, (3). To make the traditional games as the stimulus of tourism, (4). To give a special characteristics.